A LITERATURE REVIEW: THE EFFECT OF AUDIO-VISUAL AND LEAFLET COUNSELLING ON SMOKING CESSATION KNOWLEDGE AND ATTITUDE IN YOUTH COMMUNITIES - Nasir, Ardiansyah Jumaedi; Nur Djannah, Sitti; Handayani, Lina (Universitas Ahmad Dahlan, 2024)
Background: Indonesia faces a serious threat due to the increasing number of smokers. Based on data BPS for 2020-2022, the percentage of people who smoke in Yogyakarta City is 23.97%, an increase from 24.54% in 2021. However, the proportion of children and adolescents aged 12 to 21 years who smoke is increasing in Sleman Regency. Furthermore, this increase represents a 16.1% increase in the approximately 200,000 youth living in Sleman District. Methods: The purpose of this study was to determine the effect of audiovisual counseling and leaflets on adolescents' knowledge and attitudes toward smoking cessation decisions in Candibinangun Pakem Village. Using Systematic Literature Review (SLR) research design. National and international literature indexes